Released Exosomes Contribute to the Immune Modulation of Cord Blood-Derived Stem Cells - Hu, Wei; Song, Xiang; Yu, Haibo; Sun, Jingyu; Zhao, Yong (Frontiers in Immunology, 2020)
Background: Clinical studies demonstrated the immune modulation of cord blood-derived stem cells (CB-SC) for the treatment of type 1 diabetes and other autoimmune diseases, with long-lasting clinical efficacy. To determine the molecular mechanisms underlying the immune modulation of CB-SC, the actions of exosomes released from CB-SC were explored in this study. Methods: Exosomes were isolated from CB-SC cultures by using ultracentrifugation and confirmed with different markers. The activated T cells and purified monocytes from peripheral blood mononuclear cells (PBMC) were treated with CB-SC in the presence or absence of the purified exosomes, followed by functional and flow cytometry analysis of phenotypic changes with different immune cell markers. Results: CB-SC-derived exosomes displayed the exosome-specific markers including CD9, CD63 and Alix, at the size of 85.95  22.57 nm. In comparison with the treatment of CB-SC, functional analysis demonstrated that the CB-SC-derived exosomes inhibited the proliferation of activated PBMC, reduced the production of inflammatory cytokines, down-regulated the percentage of activated CD4+ T and CD8+ T cells, and increased the percentage of naïve CD4+ T and CD8+ T cells. Using the fluorescence dye DiO-labeled exosomes, flow cytometry revealed that exosomes preferably bound to the monocytes in the PBMC, leading to an improvement of mitochondrial membrane potential of treated monocytes. Further study indicated that the purified monocytes gave rise to spindle-like macrophages displaying type 2 macrophage (M2) surface markers and up-regulating an expression of immune tolerance-related cytokines after the treatment with exosomes. Conclusions: CB-SC-derived exosomes display multiple immune modulations and primarily on monocytes, contributing to the immune education of CB-SC in the clinical treatment of autoimmune diseases.